Automated Family-Wide Annotation of Secondary Structure Elements - Midlik, Adam; Hutařová Vařeková, Ivana; Hutař, Jan; Moturu, Taraka Ramji; Navrátilová, Veronika; Koča, Jaroslav; Berka, Karel; Svobodová Vařeková, Radka (Methods in molecular biology (Clifton, N.J.), 2019)
Secondary structure elements (SSEs) are inherent parts of protein structures, and their arrangement is characteristic for each protein family. Therefore, annotation of SSEs can facilitate orientation in the vast number of homologous structures which is now available for many protein families. It also provides a way to identify and annotate the key regions, like active sites and channels, and subsequently answer the key research questions, such as understanding of molecular function and its variability.This chapter introduces the concept of SSE annotation and describes the workflow for obtaining SSE annotation for the members of a selected protein family using program SecStrAnnotator.
Keywords: Structural alignment; Amino Acid Motifs; SecStrAnnotator; software; Protein domain; Secondary structure; Annotation; Proteins; Algorithms; Computational Biology; proteiny; katalytická doména; Secondary structure assignment; anotace sekvence; Protein family; algoritmy; Molecular Sequence Annotation; Software; Secondary structure elements; výpočetní biologie; aminokyselinové motivy; Catalytic Domain